2001
DOI: 10.3136/fstr.7.88
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Beer-Like Drink Produced by Mushroom Fermentation.

Abstract: In general, Saccharomyces cerevisiae is a main microorganism in beer brewing, because this microbe has potent ability to produce alcohol dehydrogenase. Recently, we discovered that some genera of mushroom produce alcohol dehydrogenase, and made a beer-like drink using a mushroom in place of S. cerevisiae. The highest alcohol concentration in this drink was achieved with Tricholoma matsutake (1069 mM, 4.6%). This beer-like drink contained about 0.17% ß-D-glucan, which is known to have preventive effects against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Hou and co-workers prepared a novel beverage by mixing polysaccharides extracted from BaChu mushroom with hawthorn juice and apple juice . Okamura et al reported on beer-like fermented drinks using Pleurotus ostreatus, Tricholoma matsutake, or Agaricus subrufescens instead of Saccharomyces cerevisiae as all of these fungi possess an alcohol dehydrogenase activity. , However, the unique capabilities of basidiomycetes in producing a wide range of natural flavors in beverages have been ignored for submerged cultivations so far. Because of consumers’ demand for natural food, basidiomycetes producing natural flavor compounds are ideal candidates for developing novel fermentation systems.…”
Section: Introductionmentioning
confidence: 99%
“…Hou and co-workers prepared a novel beverage by mixing polysaccharides extracted from BaChu mushroom with hawthorn juice and apple juice . Okamura et al reported on beer-like fermented drinks using Pleurotus ostreatus, Tricholoma matsutake, or Agaricus subrufescens instead of Saccharomyces cerevisiae as all of these fungi possess an alcohol dehydrogenase activity. , However, the unique capabilities of basidiomycetes in producing a wide range of natural flavors in beverages have been ignored for submerged cultivations so far. Because of consumers’ demand for natural food, basidiomycetes producing natural flavor compounds are ideal candidates for developing novel fermentation systems.…”
Section: Introductionmentioning
confidence: 99%
“…4) Furthermore, some basidiomycetes produce alcohol dehydrogenase, allowing the production of wine using a mushroom. 5,6) These properties of basidiomycetes appear suitable for use in CBP. In a preliminary study, we screened some edible mushrooms for their ability to produce ethanol, and found that Flammulina velutipes was a good producer of ethanol.…”
mentioning
confidence: 99%
“…5) Furthermore, some basidiomycetes produce alcohol dehydrogenase, and hence can be used to make wine. 6,7) These properties of basidiomycetes suggest that they might be suitable for CBP.…”
mentioning
confidence: 99%